Clinical applicability of detomidine and methadone constant rate infusions for surgery in standing horses. (May 2019) - Gozalo-Marcilla, Miguel; Luna, Stelio PL; Gasthuys, Frank; Pollaris, Elke; Vlaminck, Lieven; Martens, Ann; Haspeslagh, Maarten; Schauvliege, Stijn
Abstract: Objective: To determine the required rate of a detomidine infusion (loading dose 5 μg kg −1 ; initial rate 12.5 μg kg −1 hour −1 ) added to a constant infusion of methadone (0.2 mg kg −1 ; 0.05 mg kg −1 hour −1 ) for sedation in standing horses and ponies undergoing elective surgeries with appropriate local anaesthetic techniques. Study design: Prospective, clinical study. Animals: Adult, healthy, client-owned, non-food-producing horses or ponies sedated for elective standing surgeries longer than 45 minutes. Methods: At baseline (in the stables before administration of sedative agents), at 10 minutes after sedation and every 5 minutes thereafter, ataxia, sedation and surgical condition were evaluated; each scored 0–3. These scores were used to adjust the detomidine administration rate using the Ghent Sedation Algorithm. A 10 cm visual analogue scale (VAS) was used by the main surgeon at the end of the procedure to evaluate the surgical conditions. Heart rate, systolic arterial pressure and respiratory frequency were also recorded at each time point. For statistical analysis, anova for normal, Kruskal–Wallis H-test for non-normal variables, and Mann–Whitney U test for VAS were used. Results: From the 42 horses/ponies included in this study, 28 underwent dental procedures and 14 other types of procedures. Overall, dental procedures required higher mean detomidine rates compared with other types of surgeries (16.9 ± 4.5 versus 9.0 ± 1.9 μg kg −1 hour −1 ) ( p < 0.001). Dental procedures were assigned similar VAS scores, median (range), of 7.8 (5.8–10) with other procedures, 8.7 (2.8–10). Cardiovascular changes were not clinically significant. No signs or behavioural changes of abdominal pain were observed postoperatively. Conclusions and clinical relevance: Satisfactory surgical conditions were achieved using a combination of detomidine and methadone infusions with locoregional anaesthesia, with no adverse effects. Dental procedures required higher detomidine dose rates compared with other surgeries.